Faktor-faktor Penyebab Alexithymia pada Remaja: Literature Review - I Gusti Ayu Agung Mirah Pradnyadewi; Putu Nugrahaeni Widiasavitri (Universitas Muria Kudus, 2023)
The cases of alexithymia in adolescents in Indonesia increasingly occur. The impact of alexithymia, certainly, significantly affects the quality of life of a teenager. Alexithymia is not a mental disorder, but a phenomenon that can be one of the symptoms of certain mental disorders, thus making the sufferers unable to recognize, feel and identify their emotions. This study aims to determine the factors that cause alexithymia in adolescents. The method used in this study is a literature review concerning alexithymia as the theme. The article search sources were accessed from PubMed and Google Scholar library sources, limiting the years of article publication between 2015-2022. The result of this study is that there are number of factors causing alexithymia, including psychogenic factors (attachment styles, trauma, and chronic illness or pain); biogenic factors (prenatal substances or poisons, and brain structure); primary alexithymia factors (personality); as well as secondary alexithymia factors (stress, anxiety, and fatigue). Kasus alexithymia pada remaja di Indonesia kian marak terjadi. Dampak alexithymia tentunya sangat mempengaruhi kualitas kehidupan seorang remaja. Alexithymia bukanlah suatu gangguan mental, melainkan fenomena yang dapat menjadi salah satu gejala dari gangguan mental tertentu, sehingga membuat penderitanya tidak mampu mengenali, merasakan dan mengidentifikasi emosinya. Penelitian ini bertujuan untuk mengetahui faktor-faktor penyebab alexithymia pada remaja. Metode yang digunakan dalam tulisan ini yaitu literature review dengan tema alexithymia. Sumber pencarian artikel diakses pada sumber pustaka PubMed dan Google Scholar dengan tahun penerbitan artikel antara tahun 2015-2022. Hasil dari tulisan ini adalah terdapat faktor-faktor penyebab alexithymia, antara lain; faktor psikogenik (gaya kelekatan, trauma, dan penyakit atau nyeri kronis); faktor biogenik (zat-zat atau racun pra-kelahiran, dan struktur otak); faktor alexithymia primer (kepribadian); serta faktor alexithymia sekunder (stres, kecemasan, dan kelelahan)